(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The fast evolution of disruptive technology poses enormous demands and difficulties for organisations. They need to make massive changes to the OS, business models, and Organisational structure if they want to reap the advantages of new technologies and stay competitive. But technology is changing at a rapid pace, transforming industries and business settings. Disruptive technologies will continue to be a big deal in the years to come. As a result, modern corporate leadership is preoccupied with the idea of game-changing innovations that have the potential to outperform current solutions. This work fills that need by methodically synthesizing relevant prior research. Thirteen papers published between 2016 and 2018 were included in this systematic literature evaluation. The article contends that businesses can’t afford to lag behind in this fast-paced industry and must adapt by integrating digital technology, processes, and capabilities intelligently across all departments and levels. However, adapting to new, potentially game-changing technology is only part of the story. Companies should also alter the way they manage and think about long-term strategy. It addresses the ongoing need to transform the attitudes of leaders and foster staff evolution in order to gain a competitive edge.